2010
DOI: 10.1007/s11693-010-9053-4
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic biology approach allows inducible retrotransposition in whole plants

Abstract: Retrotransposons are mobile genetic elements that transpose by reverse transcription of element RNA, followed by insertion of the cDNA into new positions of the host genome. Although they are major constituents of eukaryotic genomes, many facets of their biology remain to be understood. Transposition is generally rare, suggesting that it is subject to tight regulation. However, only the first regulatory step (transcriptional induction) is currently amenable to investigation in higher eukaryotes. To investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…When a full-length copy of this TE was transferred into the Arabidopsis genome, the element was active and fully capable of transposition (Hirochika et al, 2000;Böhmdorfer et al, 2010). However, this transposition was only observed after selection in tissue culture (where TE silencing is compromised; Tanurdzic et al, 2008), in a chromatin mutant, or when an inducible promoter is used to force TE expression, demonstrating that there is repression or silencing of this TE in wild-type Arabidopsis.…”
Section: Exogenous Tes Circumvent Identity-based Rddm and Are Targetementioning
confidence: 99%
See 4 more Smart Citations
“…When a full-length copy of this TE was transferred into the Arabidopsis genome, the element was active and fully capable of transposition (Hirochika et al, 2000;Böhmdorfer et al, 2010). However, this transposition was only observed after selection in tissue culture (where TE silencing is compromised; Tanurdzic et al, 2008), in a chromatin mutant, or when an inducible promoter is used to force TE expression, demonstrating that there is repression or silencing of this TE in wild-type Arabidopsis.…”
Section: Exogenous Tes Circumvent Identity-based Rddm and Are Targetementioning
confidence: 99%
“…We stably transformed wild-type Col with an inducible full-length form of Tto (Böhmdorfer et al, 2010), which is targeted for silencing (iTto; see below; Figures 3 and 4). We then retransformed these iTto lines with the solo Tto LTR Dpro transgene from Figure 2A and found that this newly introduced TE is now targeted for identity-based (expression-independent) RdDM ( Figure 2E).…”
Section: Exogenous Tes Circumvent Identity-based Rddm and Are Targetementioning
confidence: 99%
See 3 more Smart Citations